Phenotypic characterizations of Indonesia Native Chicken With Different Combs - Maharani, Dyah; Insani, Galuh Adi; Adinda, Laurentia (2018)
The study was conducted to characterize the phenotypic appearance of Indonesian native chickens with difference combs. A total forty chickens were divided onto four groups based on comb type: single, pea, rose and walnut. Qualitative data were tabulated onto head, body and tail parts, and analysed statisticaly using desciptive statistics. As a results, beak color of chicken was vary from dark yellow, light yellow, pale yelow and white. The dark yellow of beak was dominated by chicken with single comb (40%). Light yellow mostly found in chicken with rose comb and, walnut have dominantly pale yellow (50%). Only Chicken with single and pea have white beak color in a few percentage (10%). All comb types of chicken have dark eye color. Chicken with single, pea and walnut combs dominantly have red brown crown color 50%, 40% and 80%, respectively. Chickens with rose comb were most found havnig red crown color (50%). Similary in neck feather color was dominated by single, pea and walnut. Chickens with rose comb indicated yellow (50%) and red crown (40%) color. For chest feather color, chicken with single and walnut comb were dominanted black color (50% and 40%, respectively). The pea and rose comb of chicken mostly have whitebrown (40%) and red (40%) color of chest feather. For abdomen feather color, chicken with single (50%), pea (40%) and walnut (40%) were mostly have black color, but chicken with rose comb indicated mostly red (40%). Similary in back feather color, balck feather was dominated in single, pea and walnut. Both primer and seconder wing feather color were found black in all comb types. The tail feather color was vary, chicken with single comb was dominantly have black color (40%).Chicken with rose and walnut comb have black-white tail feather, 50% and 60%, respectively. Most of chicken with pea comb have black-green tail feather color. All the comb type dominantly have black thigh color. Inconclusion, this study may provide an important view for designing conservation and breeding strategies to efficiently protect and utilize the existing variation phenotypics among local chicken populations.